Educational Development of Muslim Minority: With Special Reference to Muslim Concentrated States of India - Narula, Manju (Journal of Education and Research, 2014)
In India the National Minority Commission has identified Muslims as minorities along with Christians, Sikhs, Buddhists and Jains on the basis of religion. Out of these religious minorities Muslims are the largest ones. In spite of being the largest minority they are lagging behind in education in comparison with other religious minorities. Literacy which is a first step to education is lowest of the Muslim minority and inter-state variation in their literacy rates is also very high. Also, their literacy rate in some of the states is abysmally low. In the light of these contexts, this paper presents a brief discussion of policies and programs implemented for the development of education of the Muslim minority. Thereafter, the paper tries to portray the progress of school education in terms of access, participation, retention of Muslim children in the Muslim concentrated states. The paper suggests that strategies for their educational development should be adopted according to the need of the state/district/area. Finally, the areas of intervention and challenges are discussed and appropriate measures are suggested to improve and promote the education of Muslims in India.DOI: http://dx.doi.org/10.3126/jer.v4i1.10729Journal of Education and Research, March 2014, Vol. 4, No. 1, pp. 93-108